Efl undergraduate students’ self-regulation in thesis writing: help-seeking and motivation-regulation - Mbato, Concilianus Laos; Cendra, Anastasia (LPPM Universitas Mercu Buana Yogyakarta, 2019)
Type Undergraduate thesis writing necessitates EFL students to self-regulate themselves, particularly in overcoming the difficulties they encounter and maintaining their motivation. To date, there has been little research on EFL undergraduate students’ self-regulation, help-seeking, and motivation-regulation in thesis writing, especially in Asian context. Under explanatory mixed-method framework, this research aimed to investigate how Indonesian EFL undergraduate students self-regulated their thesis writing process and to what extent their self-regulation assisted them to seek help and regulate their motivation. The results showed that the students generally demonstrated a high level of self-regulation, help-seeking, and motivation-regulation. Furthermore, it was revealed that self-regulation had a positive, significant, and moderate correlation with help-seeking (r=.461), and a positive, significant, and high correlation with motivation-regulation (r=.648). The findings suggested that self-regulation, help-seeking, and motivation-regulation were important for students to finish their challenging undergraduate thesis. However, even when the overall measured results were good, the support from other people including from the university staff were needed, especially in cultivating students’ self-regulatory mechanism. This research offers implications for the university and thesis advisors.